Error Analysis On The Pronunciation Of Past Tense Endings (-ED) By Eleventh Grade Students At SMA N 14 Medan - Hia, Orani Adel Valentina; Simarmata, Rina Octavia; Manurung, Lastri Wahyuni (Jurnal Kajian Ilmu Pendidikan (JKIP), 2026)
This study investigates the types and causal factors of pronunciation errors in the realization of the regular past tense suffix -ed among eleventh-grade students at SMA Negeri 14 Medan. Adopting a qualitative descriptive approach, this study employed Error Analysis as its primary analytical framework, guided by Corder (1981) and the Surface Strategy Taxonomy of Dulay, Burt, and Krashen (1982). Data were collected from ten purposively selected students of class XI.2 through an oral pronunciation test comprising 60 regular past tense verbs representing the three allophones of -ed (/t/, /d/, and /ɪd/), yielding a total corpus of 600 pronunciation tokens. Semi-structured interviews were subsequently conducted to triangulate the findings and identify the sources of error. The results reveal three types of pronunciation errors: misformation (50.50%), addition (21.17%), and omission (10.00%), with an overall error rate of 81.67%. A cross-categorical analysis demonstrated a clear hierarchy of difficulty: /t/ (100%) > /d/ (87%) > /ɪd/ (58%), reflecting an inverse relationship between allophonic difficulty and orthographic transparency. Two interacting causal factors were identified: interlingual interference from Indonesian, manifested through orthographic reading habits and the absence of word-final voicing distinctions in L1, and intralingual overgeneralization driven by the near-total absence of explicit phonological instruction. These findings underscore the urgent need for targeted phonological instruction that explicitly addresses the voiced-voiceless distinction and the allophonic conditioning rules governing -ed pronunciation.